PENGARUH K3 ( KESEHATAN DAN KESELAMATAN KERJA ) DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DI DIREKTORAT JENDERAL PERUMAHAN KEMENTERIAN PEKERJAAN UMUM JAKARTA SELATAN - Dede Kurnia K. S; Kenny Astria (Jurnal Menara, 2025)
This study aims to determine the effect of K3 and Workload on employee performance at the Directorate General of Housing, Ministry of Public Works, South Jakarta, partially and simultaneously. The method used is associative with saturated sampling technique on 55 respondents. Data analysis includes validity, reliability, classical assumptions, regression, correlation coefficient, determination coefficient, and hypothesis testing. The results of the study show that K3 has a significant effect on employee performance with the regression equation Y = 10.443 + 0.778X1, correlation value 0.928, and determination coefficient 86.2%, with t count 3.769> t table 2.005. Workload also has a significant effect with the equation Y = 8.470 + 0.834X2, correlation 0.929, determination coefficient 86.4%, and t count 3.866> t table 2.005. Simultaneously, K3 and Workload have a significant effect on employee performance with the equation Y = 8.281 + 0.397X1 + 0.437X2, correlation value 0.945, coefficient of determination 89.3%, and F count 216.662 > F table 4.020. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis is accepted, meaning that there is a significant effect of K3 and Workload both partially and simultaneously on employee performance.